Seksio Sesarea pada Wanita G3P2A0 Hamil 34 minggu dengan Preeklamsia Berat dan Perdarahan Intraserebral Spontan - Apsari, Ratih Kumala Fajar; Rahardjo, Sri; Gunawan, Fanny (This journal is published by the Department of Anesthesiology and Intensive Therapy of Faculty of Medicine, Public Health and Nursing, in collaboration with the Indonesian Society of Anesthesiology and Intensive Therapy , Yogyakarta Special Region Br, 2021)
A 32-year-old woman, G3P2A0, at 34 weeks of gestation came to Sardjito hospital emergency department with complaints of not being able to speak and right limb weakness since 8 hours before entering the hospital. Patient have hypertension since before pregnancy. CT-scan result obtain bleeding in the parietal lobes sinistra and basal nuclei with a bleeding volume 60 cc accompanied by midline shifting. Patient was diagnosed with superimposed severe preeklamsia, coma cum dekstra lateralization, and spontaneous intracerebral hemmorhage. Section cesarean and craniectomy hematoma evacuation then was performed. Postoperatively, patient was treated in the ICU and then transferred to the stroke unit.